2014
DOI: 10.1111/prd.12043
|View full text |Cite
|
Sign up to set email alerts
|

Sinus floor elevation utilizing the transalveolar approach

Abstract: A transalveolar approach for sinus floor elevation with subsequent placement of dental implants was first suggested by Tatum in 1986. In 1994, Summers described a different transalveolar approach using a set of tapered osteotomes with increasing diameters. The transalveolar approach of sinus floor elevation, also referred to as 'osteotome sinus floor elevation', the 'Summers technique' or the 'Crestal approach', may be considered as being more conservative and less invasive than the conventional lateral window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 23 publications
4
80
0
Order By: Relevance
“…Maxillary sinus floor elevation using the transalveolar approach cannot be conducted under direct vision, and postoperative complications are often discussed by scholars. Maxillary sinus perforation is the most common complication of maxillary sinus floor elevation using the transalveolar approach . Endoscopic findings showed that the maxillary sinus mucosa could be elevated by 5‐mm without perforation .…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary sinus floor elevation using the transalveolar approach cannot be conducted under direct vision, and postoperative complications are often discussed by scholars. Maxillary sinus perforation is the most common complication of maxillary sinus floor elevation using the transalveolar approach . Endoscopic findings showed that the maxillary sinus mucosa could be elevated by 5‐mm without perforation .…”
Section: Discussionmentioning
confidence: 99%
“…Similar bone gain around both implant surfaces was reported (4.0 ± 1.6 mm and 4.4 ± 1.7 mm respectively) after 1‐year follow‐up. The main challenge in SFE procedures is to avoid the perforation of the Schneiderian membrane (Pjetursson & Lang 2014). It has been reported that L‐PRF can be used to cover the perforation since it has a good intrinsic adherence to the Schneiderian membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The drawbacks of this technique are the limited intra‐operative complication management and the, although rare, complication of benign paroxysmal positional vertigo (BPPV). It includes the displacement of otoliths by vibratory forces transmitted by osteotomes and mallet along with the hyperextension of the head during the operation, causing them to float around in the endolymph (Akcay, Ulu, Kelebek, & Aladag, ; Giannini et al., ; Pjetursson & Lang, ). Unexpectedly, the data of this study shows that this technique causes the most post‐operative pain during the first two post‐operative days.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, tSFE procedures are predominantly used when the RBH is >5 mm, as a lesser remaining bone height may not allow a primary implant stability (Pjetursson & Lang, ). However, recently tSFE have been successfully used in patients with less RBH (Nedir et al., ; Si et al., ) and extreme cases (Nedir et al., ).…”
Section: Discussionmentioning
confidence: 99%